Kajian Lingkungan Pembangunan Gedung Bertingkat di Daerah Istimewa Yogyakarta - Rahman, Fathin Aulia; Wahyudi, Widi; Anwar, Syaiful (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2023)
Yogyakarta Special Region is widely known as a student, tourist, and cultural city. These conditions triggered Yogyakarta’s development and growth to be very rapid. So environmental problems arise, which, if not immediately addressed, will worsen environmental conditions. The type of research carried out was descriptive-qualitative through observation and interviews. The research results showed that many developments violated legal and environmental rules. The environmental impacts that occur include a reduction in the amount of green open land, a reduction in water catchment areas, sanitation problems, groundwater availability, and river pollution. Disaster risks arising from development include landslides on river borders due to development, flooding, and land shifts. Efforts that need to be implemented to manage and prevent environmental damage include the implementation of environmental and social management systems, the implementation of institutional functions, and efforts to develop community capacity through training and community education. Meanwhile, efforts are being made to reduce disaster risk through physical mitigation, biological mitigation, and the mitigation of social, economic, and cultural impacts.